Ensemble Prediction of a Halo Coronal Mass Ejection Using Heliospheric Imagers. Issue 7 (2nd July 2018) - Amerstorfer, T.; Möstl, C.; Hess, P.; Temmer, M.; Mays, M. L.; Reiss, M. A.; Lowrance, P.; Bourdin, P.‐A.
Abstract: The Solar TErrestrial RElations Observatory (STEREO) and its heliospheric imagers (HIs) have provided us the possibility to enhance our understanding of the interplanetary propagation of coronal mass ejections (CMEs). HI‐based methods are able to forecast arrival times and speeds at any target and use the advantage of tracing a CME's path of propagation up to 1 AU and beyond. In our study, we use the ELEvoHI model for CME arrival prediction together with an ensemble approach to derive uncertainties in the modeled arrival time and impact speed. The CME from 3 November 2010 is analyzed by performing 339 model runs that are compared to in situ measurements from lined‐up spacecraft MErcury Surface, Space ENvironment, GEochemistry, and Ranging and STEREO‐B. Remote data from STEREO‐B showed the CME as halo event, which is comparable to an HI observer situated at L1 and observing an Earth‐directed CME. A promising and easy approach is found by using the frequency distributions of four ELEvoHI output parameters, drag parameter, background solar wind speed, initial distance, and speed. In this case study, the most frequent values of these outputs lead to the predictions with the smallest errors. Restricting the ensemble to those runs, we are able to reduce the mean absolute arrival time error from 3.5 ± 2.6 to 1.6 ± 1.1 hr at 1 AU. Our study suggests that L1 may provide a sufficient vantage point for an Earth‐directed CME, when observed by HI, and that ensemble modeling could be a feasible approach to use ELEvoHI operationally. Plain Language Summary: The most intense geomagnetic storms are caused by coronal mass ejections (CMEs), also known as solar storms. Electrical power outages, malfunctions of the global navigation satellite system, or disturbances of the radio transmission signal can be the consequences of strong geomagnetic storms. Therefore, it is of high importance to be able to predict the arrival of CMEs at Earth as accurate as possible. Usually, predictions of these arrivals are based on observations from a small region around the Sun covering a distance of up to 15% of the Sun‐Earth distance. Currently, these predictions result in an error in arrival time of about 10 hr. Our study is based on observations of the so‐called heliospheric imagers (HIs) on board the National Aeronautics and Space Administration Solar TErrestrial RElations Observatory mission and observe the whole space between the Sun and 1 AU (astronomical unit; distance between Sun and Earth). We present a new way of using the HI‐based prediction utility ELEvoHI to predict the arrivals of CMEs. We found that using an ensemble approach (339 predictions for the same event with different input parameters) leads to an accurate prediction and could be used in real time for future missions carrying an HI instrument. Key Points: Heliospheric imaging at the Sun‐Earth L1 point may be supplementary to an operational space weather mission at L5 Information on the ecliptic extent of a CME improves HI‐based predictions ELEvoHI ensemble prediction can be restricted by considering frequency distributions of internal fitting parameters